Applying augmented reality in teaching and learning / Umi Hanim Mazlan ... [et al.] - Mazlan, Umi Hanim; Ibrahim, Izleen; Ghazali, Nurulhuda; Zulkifli, Zalikha; Ahmad, Samsiah; Wan Ismail, Wan Saiful‘Azzam (UiTM Cawangan Perlis, 2017)
In this era of teaching and learning, most students are fond of interactive learning compared to traditional lectures that uses whiteboard and marker pen. Because of that, educators need to be more creative in preparing their teaching material in order to attract students’ attention during teaching and learning process. With the technology advancement, there is variety of software that can help educators to produce a creative material. Augmented reality, AR, is technology where virtual reality is combined with the real world. The main devices for AR are displays, computers, input and tracking devices but recent advances in smartphone technology making them suitable as an AR platforms. This augmentation technique seems relevant to be applied in teaching field because it will help teachers to develop a dynamic material that is capable to capture students’ attention, engagement and participation in a classroom. In addition, AR is very helpful in learning process where students can always listen and view the lecture videos anytime they pleased. This is suitable for blended learning purpose where students can learn on their own with less supervision from lecturers. Therefore, this paper reviews the AR technology which can be utilized to enhance the process of teaching and learning.